2019
DOI: 10.1177/0731684418824997
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of single-walled carbon nanotubes based on various shell theories

Abstract: Carbon nanotubes are used in several engineering applications because of their superior mechanical properties. Scientific works still need to be carried out, especially on their dynamic response. These studies mainly focus on modal analysis, considering zigzag and armchair nanotubes, and sometimes, varying chirality. However, these works do not present any results on the steady-state responses. Therefore, the objective of this paper is to perform different studies, in terms of the stiffness response, modal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Since being discovered in 1993 by Iijima and Ichihashi (1993), carbon nanotubes (CNTs) are becoming increasingly popular nanomaterial because of their extremely high thermal and electrical conductivity, high mechanical strength (>150 GPa) (Hashemnia et al, 2009), and low density (2267 kg/m3) (Lee and Lee, 2012; Palacios and Ganesan, 2019; Wu et al, 2009), which gives them extremely high specific strength (150×109/22676.6×107 Nm/kg), that is, 200 times that of steel. They are being widely used to reinforce concrete beam composites (Bourada et al, 2020; Bousahla et al, 2020; Mohammadimehr et al, 2020) where they are shown to improve resistance to buckling and vibration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since being discovered in 1993 by Iijima and Ichihashi (1993), carbon nanotubes (CNTs) are becoming increasingly popular nanomaterial because of their extremely high thermal and electrical conductivity, high mechanical strength (>150 GPa) (Hashemnia et al, 2009), and low density (2267 kg/m3) (Lee and Lee, 2012; Palacios and Ganesan, 2019; Wu et al, 2009), which gives them extremely high specific strength (150×109/22676.6×107 Nm/kg), that is, 200 times that of steel. They are being widely used to reinforce concrete beam composites (Bourada et al, 2020; Bousahla et al, 2020; Mohammadimehr et al, 2020) where they are shown to improve resistance to buckling and vibration.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs are also being used for three-phase CNT/polymer/fiber laminated truncated conical shells (Yousefi et al, 2020). Such CNT-based composites have application as lightweight, high strength, vibration resilient materials in automotive, aerospace, space research, and nuclear industries (Palacios and Ganesan, 2019). Further, CNTs are used as high-frequency oscillators in nano-electromechanical systems (NEMS) such as nano-sensors, nano-resonators, charge detectors, field emitters, and nano-actuators (Gibson et al, 2007; Gupta et al, 2018; Wang and Arash, 2014; Zaporotskova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation